Enlarging the Contracting Space: Collateral Menus, Access to Credit, and Economic Activity - Campello, Murillo; Larrain, Mauricio (Review of Financial Studies, 2016)
Recent reforms across Eastern European countries have given more flexibility and information to parties to engage in secured debt transactions. The menu of assets legally accepted as collateral was enlarged to include movable assets (e.g., machinery and equipment). Generalized difference-in-differences tests show that firms operating more movable assets borrowed more as a result. Those firms also invested more, hired more, and became more efficient and profitable following the changes in the contracting environment. The financial deepening we document triggered important reallocation effects: firms affected by the reforms increased their share of fixed assets and employment in the economy. Received August 15, 2014; accepted October 23, 2015 by Editor David Denis.